2021
DOI: 10.1088/1742-6596/1992/2/022161
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an Ecological Model of Blended Assistant Teaching of College Oral English Based on “Internet +” Technology

Abstract: According to the input and output of the language as the theoretical basis, from the learning of oral English in college, construct the oral English teaching mode of students, teachers, and the Internet. Different forms of teaching modes help students increase their interest in learning English. Improve the use rate of expressing English, let students develop the role of autonomous learning and deep learning, stimulate students’ initiative through the help of the Internet, and give play to the teacher’s auxili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The auxiliary mediators in the process of reaching the potential development level are "scaffolding". "Scaffolding" can be interactive scaffolds based on interpersonal relationships such as parents, peers and teachers, or instrumental scaffolds based on Apps and multimedia, which is usually in the form of demonstration, decomposition of complex tasks, providing guidance, prompting, encouragement and feedback evaluation [6].…”
Section: Scaffolding Instruction and Innovative Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The auxiliary mediators in the process of reaching the potential development level are "scaffolding". "Scaffolding" can be interactive scaffolds based on interpersonal relationships such as parents, peers and teachers, or instrumental scaffolds based on Apps and multimedia, which is usually in the form of demonstration, decomposition of complex tasks, providing guidance, prompting, encouragement and feedback evaluation [6].…”
Section: Scaffolding Instruction and Innovative Approachmentioning
confidence: 99%
“…However, due to the limited class hours and the large scale of classes, students have no opportunity to fully practice their spoken English. Therefore, it is always difficult to improve their spoken English [6]. College Spoken English class has been faced with difficulties in effectively improving students' speaking skills for a long time [3].…”
Section: Introductionmentioning
confidence: 99%
“…Which can be easily merged, updated, added, deleted, and changed. This curriculum will create and develop a digital learning environment for educational institutions encouraging innovation in education and ICT (Shi, 2021) The experiment conducted by a group of researchers also demonstrated that "e-learning stimulation" and "social influence" had a positive effect on behavioral intention, while "favorable conditions" did not affect using the e-learning portal. Moreover, the usage behavior had a positive effect on stimulating e-learning.…”
Section: Introductionmentioning
confidence: 96%
“…At the same time, all kinds of information updated on the Internet influence the educational paradigms in traditional education, and both students and teachers are overwhelmed with rich educational resources. (Shi, 2021). Providing the digital learning environment in educational institutions involves the using of all its elements, namely: IT services, applications, systems, etc.…”
Section: Introductionmentioning
confidence: 99%
“…This can motivate students to search for materials available on the Internet outside of the formal classroom, as it leads to a higher level of education for children compared to the level provided by the traditional education system (Andrzej, 2021). So; Modern educational technology -represented by computer-assisted networked education -has a profound impact on education, at the same time the latest types of information on the Internet and constantly updated educational models influence traditional education, and provide both students and teachers with rich educational resources (Bujiao, 2021). The use of the digital learning environment for educational institutions involves the use of all its elements; including information technology services, applications, and systems that can be easily integrated, updated, added, deleted, and changed.…”
Section: Introductionmentioning
confidence: 99%